La enseñanza de la pintura en el área de educación artística en básica secundaria y media, en nueve colegios distritales de Bogotá - Arias Ayala, Johanna Esperanza (Universidad de La Salle. Facultad de Ciencias de la educación. Maestría en Docencia (incluye Maestría en Docencia - CESMAG)., 2017)
This project responds to the Macro-Arts Education Project, proposed by the Salle University in research "Education, Language and Communication". The painting is a field of study in art education, from which it is possible to cultivate the intellect and develop sensitivity; under this premise, this work focused on the teaching painting in nine public schools in the District, by reaching out to the work of teachers in the area of art education that guide painting, training, methodologies, difficulties and meaningful experiences. This qualitative descriptive research - explanatory, sought to characterize the teaching painting in the area of arts education, in order to reveal implemented methodologies, problematic situations ratings, to provide positioning of this artistic field at school. To accomplish this task, a group of nine (9) art teachers that teach painting area was selected. semistructured interview was implemented, information research significance, systemized by the method distill the information allowed from triangulation, conclude that collection: the arts are fundamental in human life, therefore, the artistic area should have the same importance as any other area of knowledge, and in particular painting favors the acquisition of knowledge and skills, as well as enabling the expression, sensitivity, understanding people and reality, contributing in this way to human development